The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12799/jkachn.2014.25.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Medication Status and the Effects of a Medication Management Education Program for the Elderly in a Community

Abstract: Purpose: This study investigated medication status by examining the effects of a medication management education program on the knowledge of medications and medication misuse behaviors in the elderly in a local community. Methods: This study used a non-equivalent control group quasi-experimental design. For the study, 116 subjects were assigned to the control group and another 116 subjects were assigned to the experimental group. The medication management education program consisted of 1:1 education, practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…This study also showed a significant reduction in medication misuse behavior in the experimental group after the AMAEP, with a pre- and post-average difference of −3.36. This is similar to the −2.81 point reduction in a study by Lee [ 11 ] and the −2.00 point difference in a study by Park et al [ 40 ] after conducting an educational program on drug misuse among older adults. The reduction in drug misuse may have been because patients with liver disease were discouraged from taking various dietary supplements or over-the-counter medications without consulting a healthcare practitioner in a number of sessions and through one-on-one education with the nurses.…”
Section: Discussionsupporting
confidence: 88%
“…This study also showed a significant reduction in medication misuse behavior in the experimental group after the AMAEP, with a pre- and post-average difference of −3.36. This is similar to the −2.81 point reduction in a study by Lee [ 11 ] and the −2.00 point difference in a study by Park et al [ 40 ] after conducting an educational program on drug misuse among older adults. The reduction in drug misuse may have been because patients with liver disease were discouraged from taking various dietary supplements or over-the-counter medications without consulting a healthcare practitioner in a number of sessions and through one-on-one education with the nurses.…”
Section: Discussionsupporting
confidence: 88%
“…Poor adherence may result in disease deterioration and failure of treatment [6]. Although the rate of polypharmacy is steadily increasing [7], current studies in Korea are limited to studying drug usage [8]. A systematic review of international research revealed a lack of investigation into medication adherence among older people with polypharmacy [9].…”
Section: Necessity Of Studymentioning
confidence: 99%
“…노인 대상의 복약관리 교육은 노인의 약물지식 및 약물 복약 이행 도 증진에 기여하며 [8], 고혈압 교육에 참여한 노인 고혈압 환자군은 참여하지 않은 군에 비해 12.4배 약물 복용 이행이 높았다 [9]. 그럼 에도 현재까지 국내에서 지역사회 노인을 대상으로 복약관리 프로그 램을 한 연구의 수가 많지 않고 고혈압 노인을 대상으로 한 중재 연 구 [10,11]는 더욱 적어, 최근 증가하고 있는 노인 고혈압 유병률을 고려하였을 때 [2] 더 많은 중재 연구의 시도가 필요하다.…”
Section: 4배 높았다unclassified
“…여야 하는데 [4] 이에 부정적인 영향을 주는 요인으로 약물에 대한 지 식 부족 [12], 약물 복용에 대한 낮은 자기효능감 [13], 의료인과의 부 족한 의사소통 [14] 등이 확인되었다. 약물에 대한 지식 부족은 약물 이행을 저해하는 주요 요인으로, 노인의 신체 및 인지적 변화와 특성 을 고려하여 대상자가 이해하기 쉬운 교육을 진행해야 한다 [8].…”
Section: 성공적인 혈압관리를 위해서는 노인의 약물치료 이행도를 증진하unclassified
See 1 more Smart Citation